AI Awareness dan Perceived Job Insecurity: Sebuah Studi Kuantitatif pada Karyawan Aktif - Hartono, Agnes Yolanda; Tanadi, Clarissa Amellia; Colin, Stephanie Olga; Saraswati, Kiky Dwi Hapsari; Oktavia, Stephanie (Jurnal Ilmiah Psyche, 2025)
The advancement of artificial intelligence (AI) technology has significantly transformed organizational structures and work dynamics, introducing new challenges for employees in adapting to digital transformation. AI is increasingly integrated into various workplace systems and is influencing the role of human labor in organizations. This study aims to examine the relationship between AI awareness and perceived job insecurity among active employees from various professional fields. Using a quantitative approach with a correlational design, data were collected from 130 participants through an online questionnaire that included validated scales measuring AI Awareness and Job Insecurity. Normality tests showed that the data were not normally distributed; therefore, the hypothesis was tested using Spearman’s correlation analysis. The results revealed a strong and significant positive relationship between AI awareness and perceived job insecurity (r = 0.714, p < 0.001). These findings suggest that higher awareness of AI’s roles and impacts is associated with a greater sense of job insecurity, both in quantitative and qualitative aspects. Theoretically, this research contributes to the growing body of knowledge on the psychological effects of technological developments. Practically, the findings highlight the importance of implementing more human-centered change management strategies, including transparent communication and psychological support for employees. The study’s limitations include the use of non-probability sampling and a relatively small sample size, which restrict generalizability. Future research is recommended to broaden the sample scope across work sectors and to explore potential mediating or moderating variables in the relationship between AI awareness and job insecurity.